Sustainable limits to crop residue harvest for bioenergy: maintaining soil carbon in Australia's agricultural lands. Issue 3 (8th March 2014) - Zhao, Gang; Bryan, Brett A.; King, Darran; Luo, Zhongkui; Wang, Enli; Yu, Qiang
Abstract The use of crop residues for bioenergy production needs to be carefully assessed because of the potential negative impact on the level of soil organic carbon (SOC) stocks. The impact varies with environmental conditions and crop management practices and needs to be considered when harvesting the residue for bioenergy productions. Here, we defined the sustainable harvest limits as the maximum rates that do not diminish SOC and quantified sustainable harvest limits for wheat residue across Australia's agricultural lands. We divided the study area into 9432 climate‐soil (CS) units and simulated the dynamics of SOC in a continuous wheat cropping system over 122 years (1889 – 2010) using the Agricultural Production Systems sIMulator (APSIM). We simulated management practices including six fertilization rates (0, 25, 50, 75, 100, and 200 kg N ha−1) and five residue harvest rates (0, 25, 50, 75, and 100%). We mapped the sustainable limits for each fertilization rate and assessed the effects of fertilization and three key environmental variables – initial SOC, temperature, and precipitation – on sustainable residue harvest rates. We found that, with up to 75 kg N ha−1 fertilization, up to 75% and 50% of crop residue could be sustainably harvested in south‐western and south‐eastern Australia, respectively. Higher fertilization rates achieved little further increase in sustainable residue harvest rates. Sustainable residue harvest rates were principally determined by climate and soil conditions, especially the initial SOC content and temperature. We conclude that environmental conditions and management practices should be considered to guide the harvest of crop residue for bioenergy production and thereby reduce greenhouse gas emissions during the life cycle of bioenergy production.